2020
DOI: 10.18632/oncotarget.27856
|View full text |Cite
|
Sign up to set email alerts
|

Damage-associated molecular pattern (DAMP) activation in melanoma: investigation of the immunogenic activity of 15-deoxy, Δ12,14 prostamide J2

Abstract: Damage-associated molecular pattern (DAMP) activation in melanoma: investigation of the immunogenic activity of 15-deoxy, Δ 12,14 prostamide J 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…On the other hand, the inhibition of IRE1 or ATF6 did not suppress 15d-PMJ 2 -induced cell death. Moreover, a previous study from our group revealed that PERK was required for ER stress, apoptosis, and the emission of damage associated molecular patterns (DAMPs), which caused dendritic cell maturation [ 42 ]. Hence, our collective findings shed light on the importance of PERK in 15d-PMJ 2 -mediated death and downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the inhibition of IRE1 or ATF6 did not suppress 15d-PMJ 2 -induced cell death. Moreover, a previous study from our group revealed that PERK was required for ER stress, apoptosis, and the emission of damage associated molecular patterns (DAMPs), which caused dendritic cell maturation [ 42 ]. Hence, our collective findings shed light on the importance of PERK in 15d-PMJ 2 -mediated death and downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, noteworthy in melanoma would be the emerging cytotoxic role of an endocannabinoid metabolite: 15‐deoxy, Δ12,14 prostamide J2 (15dPMJ2). The latter, acting as a sort of “super‐alarmin” would trigger, in an endoplasmic reticulum stress‐dependent manner, the exposure of damage‐associated molecular patterns (including cell surface CRT, ATP, HMGB1, HSP70 and HSP90) resulting in the recruitment and activation of APCs and activation of the anti‐tumor T cell immune response, thus eliciting an immunogenic cell death response 106 …”
Section: Introductionmentioning
confidence: 99%
“…Promotion of cellular oncogenic events via upregulation of EGFR and EGFR2 and tumor progression via YB-1 and NF-κB activation78 Anti-tumoral Supporting the killing activity of NK cells78 Li Pomi et al79 HMGB1 Pro-tumoral Promotion of neoangiogenesis and pro-tumoral immunity (via IL-10-producing M2 macrophages), upregulation of proinflammatory cytokines IL-23 and IL-17, and suppression of cytotoxic T-cell activity (via the RAGE/HMGB1 axis)79 (Continues)The latter, acting as a sort of "super-alarmin" would trigger, in an endoplasmic reticulum stress-dependent manner, the exposure of damage-associated molecular patterns (including cell surface CRT, ATP, HMGB1, HSP70 and HSP90) resulting in the recruitment and activation of APCs and activation of the anti-tumor T cell immune response, thus eliciting an immunogenic cell death response 106. 2 | DISCUSS IONFrom our critical analysis focusing on the investigated functional role and related clinical importance of each alarmin in cutaneous malignant melanoma so far, a more conclusive view has emerged for some alarmins and so for others.…”
mentioning
confidence: 99%
“…Our group identified a novel molecule produced from the metabolism of AEA by COX-2 named 15-deoxy-Δ 12,14 prostamide J 2 (15d-PMJ 2 ) (Soliman et al, 2016;Ladin et al, 2017). 15d-PMJ 2 activates apoptotic ER stress and ER stress-dependent exposure of damage associated molecular patterns (DAMPs) (Ladin et al, 2022;Elhassanny et al, 2020). The induction of ER stress by 15d-PMJ 2 is primarily mediated by PERK signaling which causes the release of ERresident Ca 2+ and Ca 2+ overload in the mitochondria leading to ER-stress dependent apoptosis (Ladin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%